Comparative Study on Human Development Index (HDI): Indonesia and Bangladesh Context - Nulhaqim, Soni Ahmad; Kamrujjaman, M D (Share : Social Work Journal, 2013)
The Human Development Index (HDI) is a development indicator since 1990, operated by theUnited Nations Development Programme. Our entitled âComparative Study on HumanDevelopment Index (HDI): Indonesia and Bangladesh Contextâ paper will focus oncomparison of both countries situation. In common scenes Indonesia is in advance thanBangladesh but what is the real situation are exist in both countries will be explained by ourstudy. Here we will compare series data (1980-2011) & its trends, value comparison (2011-2012), of two countries. In this paper we have analysis following segments of two countriesnamed Inequality-adjusted HDI(IHDI), Gender Inequality Index (GII), Multidimensional PovertyIndex (MPI) and Cross-Analysis of Indonesia & Bangladesh related to others relevant data like:Demographic Situation, Education Condition, Health Situation, Gender Observation etc. In ourpaper we have used New method for 2011 data onwards that Published on 4 November 2010(and updated on 10 June 2011), starting with the 2011 Human Development Report the HDIcombines three dimensions: A long and healthy life: Life expectancy at birth, Education index:Mean years of schooling and Expected years of schooling, A decent standard of living: GNI percapita (PPP US$). Hopefully this paper will give us a clear idea about two countries currentsocio-economic condition as well.